RETRACTED : Urban Expansion Analysis and Land Use Changes in Rangpur City Corporation Area, Bangladesh, using Remote Sensing (RS) and Geographic Information System (GIS) Techniques - Md Naimur Rahman (Geosfera Indonesia, 2019)
This article has been retracted at the request of managing editor. REASON: One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not prepared and/or appeared in any other publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process. Similar article has appeared in http://www.ijasrw.com/pdf/Oct19/ij43.pdf This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License